2008
DOI: 10.1007/s00213-008-1345-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the H3 receptor inverse agonist thioperamide on cocaine-induced locomotion in mice: role of the histaminergic system and potential pharmacokinetic interactions

Abstract: The present results indicate that histamine released by thioperamide through the blockade of H3 autoreceptors is not involved in the ability of this compound to potentiate cocaine induced-hyperactivity. Our data suggest that thioperamide, at least at 10 mg/kg, increases cocaine-induced locomotion through the combination of pharmacokinetic effects and the blockade of H3 receptors located on non-histaminergic neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…H3R antagonists modulate also the effects of other drugs such as cocaine (Brabant et al, 2005(Brabant et al, , 2006(Brabant et al, , 2009Clapham and Kilpatrick, 1994) and amphetamine (Munzar et al, 1998(Munzar et al, , 2004. However, one of the probable mechanisms underlying the changes in cocaine responses might be the interaction of the imidazole-based H3R antagonists with the liver cytochrome P-450 enzymes resulting in higher concentration of cocaine in the blood (Brabant et al, 2009). We have not detected H3R ligand-induced alterations in plasma alcohol concentrations suggesting that H3R antagonism could be beneficial in the treatment of alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…H3R antagonists modulate also the effects of other drugs such as cocaine (Brabant et al, 2005(Brabant et al, , 2006(Brabant et al, , 2009Clapham and Kilpatrick, 1994) and amphetamine (Munzar et al, 1998(Munzar et al, , 2004. However, one of the probable mechanisms underlying the changes in cocaine responses might be the interaction of the imidazole-based H3R antagonists with the liver cytochrome P-450 enzymes resulting in higher concentration of cocaine in the blood (Brabant et al, 2009). We have not detected H3R ligand-induced alterations in plasma alcohol concentrations suggesting that H3R antagonism could be beneficial in the treatment of alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…We repeated the experiment with another H3 agonist, immepip (39). Administration of SKF82958 and immepip (20 mg/kg) produced the same pattern of results as RAMH.…”
mentioning
confidence: 98%
“…One study found enhanced PPI following administration of both thioperamide and ciproxifan in DBA/2 mice, but not in C57BL/6 mice (Browman et al, 2004). Thus, the role of H3R in PPI seems to be dependent on both the mouse strain and the use of imidazole-based H3R antagonists, which affect liver CYP450 metabolism (Brabant et al, 2009). Thus, when administered in combination with drugs, using the same route of metabolism, increased/decreased concentrations of the drugs in the blood can be detected.…”
Section: H3r Regulates Sensorimotor Gating and Dopaminergic Signalingmentioning
confidence: 99%